2007
DOI: 10.1007/bf03027070
|View full text |Cite
|
Sign up to set email alerts
|

Active vibration μ-synthesis-control of a hydrostatically supported flexible beam

Abstract: Ibis paper presents active vibration control of a hydrostatically supported, flexible beam. The objective is to show the capability of active hydrostatic bearings, where the flow rate is controlled with a fast dynamic servo valve. Consequently the damping as well as the stiffness behaviour of the supported structure should be improved. First the damping behaviour is increased by using acceleration feedback in combination with the modem, robust control concept -synthesis. It enables to overcome undesirable prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The dynamics of the hoisting rope are modeled as an axially-moving string system. The trolley movement to its target position, which is made by rotating the trolley drum in the clockwise or counter clockwise directions, gives rise to lateral vibrations of the rope (due to flexibility) as well as the sway motion of the spreader [15]. It is assumed that the motions of both the spreader and the rope occur in a vertical plane, that is, the X-Y plane in Fig.…”
Section: System Dynamicsmentioning
confidence: 99%
“…The dynamics of the hoisting rope are modeled as an axially-moving string system. The trolley movement to its target position, which is made by rotating the trolley drum in the clockwise or counter clockwise directions, gives rise to lateral vibrations of the rope (due to flexibility) as well as the sway motion of the spreader [15]. It is assumed that the motions of both the spreader and the rope occur in a vertical plane, that is, the X-Y plane in Fig.…”
Section: System Dynamicsmentioning
confidence: 99%
“…Here, it should be noted that, as scriptH2 and scriptH control methodologies are standard tools in the control community, there is not a vital need for detailed re-description of this mathematically intensive subject, where the interested reader is referred to the literatures. 1321,7783 Figure 2(a) shows the standard configuration of the multi-objective scriptH2/scriptH robust output feedback controller where boldP(s) is the generalized plant comprising the arrangement of all dynamics required for design and synthesis of the generalized controller boldK(s) based on the measurable error signal e , while w denotes the exogenous input vector to the generalized plant (e.g. reference signal, r , disturbances, d , noise, n , etc., see Figure 2(b)).…”
Section: Formulationmentioning
confidence: 99%
“…Here, the objective is to achieve a high disturbance rejection by limiting the closed-loop sensitivity function, boldSfalse(sfalse) over the control bandwidth. 77 Also, noting that the actuator control signal cannot be boundless, the control effort u should be appropriately confined for proper controller realization. Thus, one should limit the corresponding control effort described by boldKfalse(sfalse)boldSfalse(sfalse).…”
Section: Formulationmentioning
confidence: 99%
“…In case of a thrust hydrostatic or hybrid bearing is the scheme is even more simplified because the rotor motion needs to be controlled only along one axis that coincides with the direction of the bearing circumference axis. Example of a thrust bearing with active control research can be found in [16].…”
Section: Types and Main Features Of Active Bearingsmentioning
confidence: 99%